SOME ANAYSIS OF TOURISM TEXTS (World Bulletin of Social Sciences, 2022)
Studying the most effective means of conveying and influencing travel texts to consumers in Uzbek and English language cultures is of particular interest in this research. In this article, we present Uzbek and English travel texts we will consider and compare some syntactic constructions